Cultural Integration and Political Consciousness in Qur’anic Exegesis: A Study of the Tafsīr Al-Qur’ān Al-Karīm by Binjai’s Ulama Tiga Serangkai - Randy Putra Alamsyah; Daud Lintang (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2025)
This study examines the Tafsīr Al-Qur'an Al-Karīm authored by the Binjai’s Ulama Tiga Serangkai, Abdul Halim Hasan, Zainal Arifin Abbas, and Abdurrahim Haitami, within the framework of belief systems, cultural integration, and socio-political dynamics in Indonesia. Employing a critical hermeneutic approach and historical discourse analysis, the research investigates how this tafsīr not only interprets sacred texts but also functions as a medium for fostering socio-political consciousness among Muslims. The primary data source is the tafsīr text itself, supported by secondary literature on Qur’anic exegesis in Indonesia and historical studies of the period in which the work emerged. Findings reveal that the tafsīr combines tafsīr bi al-ma’thūr and tafsīr bi al-ra’y methodologies, with a strong emphasis on themes such as jihād, Islamic leadership, and the unity of the ummah. The work illustrates the adaptability of Islamic teachings within diverse social contexts and reflects a critical stance against colonialism and Western cultural hegemony. It also advocates for ethical Muslim leadership. This tafsīr remains pertinent to contemporary Islamic discourse in Indonesia, particularly in areas concerning social justice, political reform, and the interface between Islam Nusantara and transnational Islam. By situating text within context, this work exemplifies how tafsīr can serve both as spiritual guidance and as a vehicle for social transformation.